IMPACT OF REMINISCENCE THERAPY ON COGNITIVE FUNCTION IN THE ELDERLY - Meilinda Silaban; Rachmawaty M.Noer; Dhea Nur Yumanda Putri (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Cognitive decline in older adults is a global health issue that affects independence, quality of life, and increases the burden on families and healthcare systems. Reminiscence therapy, a non-pharmacological intervention, is known to be effective in stimulating long-term memory and maintaining cognitive function. This study aims to evaluate the effect of reminiscence therapy on the cognitive function of elderly people in Kampung Tua Dapur 12, Batam City. This study used a pre- experimental design with a one-group pre-test and post-test approach without a control group. A total of 24 elderly people aged ≥60 years were selected using purposive sampling. The intervention consisted of four sessions of reminiscence therapy based on Focus Group Discussions (FGD) over a two-week period. The Mini Mental State Examination (MMSE) was used to measure cognitive function before and after the intervention. Data were analyzed using a paired sample t-test. The results showed there was a significant improvement in cognitive function after the intervention (p-value = 0.000)